A consensus-based, revised and comprehensive catalogue for Mediterranean water masses acronyms - SCHROEDER, KATRIN; BEN ISMAIL , SANA; BENSI , MANUEL; BOSSE , ANTHONY; CHIGGIATO, JACOPO; CIVITARESE, GIUSEPPE; FALCIERI M, FRANCESCO; FUSCO, GIANNETTA; GAČIĆ , MIROSLAV; GERTMAN, ISAAC; KUBIN , ELISABETH; MALANOTTE-RIZZOLI, PAOLA; et al. (Mediterranean Marine Science, 2024)
Addressing the need for clear communication in Mediterranean oceanography, this study presents a revised and comprehensive catalogue of water mass acronyms. Although there is no universal set of standard rules for assigning acronyms to water masses, as these can vary among different research groups, regions, or scientific communities, scientists generally aim for clarity and consistency when naming and abbreviating water masses to facilitate communication within the scientific community. The team of experts, guided by the CIESM (the Mediterranean Science Commission) C2 Committee on the Physics and Climate of the Ocean, reviewed existing literature and established new acronyms and naming guidelines. This standardized system, emphasizing clarity and consistency, replaces the current variable practices employed by different research groups.